FOXE1 polyalanine tract length screening by MLPA in idiopathic premature ovarian failure - Qin Chun-rong; Yao Ji-long; Zhu Wen-jie; Wu Wei-qing; Xie Jian-sheng (BMC, 2011)
Abstract Background FOXE1 is one of the candidate genes for genetic predisposition to premature ovarian failure (POF) and it contains an alanine tract. Our purpose is to assess the influence of length of the alanine tract of FOXE1 on genetic susceptibility to POF. Methods The group studied consisted of 110 Chinese patients with idiopathic POF and 110 women from normal controls. The polyalanine tract and flanking sequence of FOXE1 was screened using the Multiple Ligation-dependent Probe Amplification (MLPA) technique and directly sequenced. Results Three variants of FOXE1-polyalanine length, containing 12, 14, or 16 alanine residues, and 5 different genotypes were identified. There were significantly lower frequencies of the 14/14 genotypes in cases with POF (X2 = 119.73, P = 0.001), as compared with the controls. The incidence of 16/16 genotypes of FOXE1-polyalanine was significantly higher in patients with POF (X2 = 3.403, P = 0.001) in comparison to the controls. The FOXE1 14 alanine allele was significantly less common in the POF patient group (186/220) than the controls (216/220) (X2 = 25.923, P = 0.0001). The FOXE1 16 alanine allele was significantly more common in the POF patient group (28/220) than the controls (4/220) (X2 = 19.412, P = 0.0001). Conclusion This finding provides evidence that polyalanine repeat expansions in FOXE1 may be responsible for the genetic aetiology of POF in Chinese women.